Global trade and deforestation: potential impacts of the EUDR on the Brazilian beef industry - Borges, Jose Victor de Jesus Pereira (2025)
This study analyzes the effects of global trade on deforestation. Based on georeferenced data on forest loss and agricultural and livestock production, the amount of deforestation measured between 2006 and 2010 was attributed to 42 agricultural commodities and 3 livestock commodities. A global input-output matrix was used to understand how deforestation propagates through production chains until it reaches final demand. Using input-output theory techniques, two indicators were calculated: one for deforestation generation per additional dollar in final demand, and another for the deforestation footprint of countries. Subsequently, a case study was carried out to estimate the impact of the EUDR on the Brazilian beef market, assuming the regulation had been in force at the end of 2005. The results revealed facts such as the dependence of the demand structure of poorer countries on more extractive sectors, and that richer countries consume deforestation mainly via imports. The simulated EUDR scenario pointed to an annual trade reduction of USD 38,9 million between Brazil and the EU, and a reduction of the EUs deforestation footprint by 202 hectares over five years.